2009
DOI: 10.1007/s00198-009-1047-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing forearm fracture risk in postmenopausal women

Abstract: Purpose-To test the clinical utility of approaches for assessing forearm fracture risk.Methods-Among 100 postmenopausal women with a distal forearm fracture (cases) and 105 with no osteoporotic fracture (controls), we measured areal bone mineral density (aBMD) and assessed radius volumetric BMD, geometry and microstructure using high-resolution peripheral QCT; ultradistal radius failure load was evaluated in micro-finite element (μFE) models.Results-Fracture cases had inferior bone density, geometry, microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 47 publications
9
85
2
2
Order By: Relevance
“…In a matched case-control study, significantly lower volumetric BMD values were found in patients with fractures (23). In a recent study on forearm fracture risk and a second study on fracture prediction in postmenopausal women, the discriminatory power of HR-pQCT was similar as for patients with preterminal renal failure (24,25). A remarkable difference between these studies and the data presented here is that the heterogeneity of trabecular structures was markedly higher in dialysis patients with fracture history compared with dialysis patients without a history of fracture, especially in women.…”
Section: Discussionmentioning
confidence: 89%
“…In a matched case-control study, significantly lower volumetric BMD values were found in patients with fractures (23). In a recent study on forearm fracture risk and a second study on fracture prediction in postmenopausal women, the discriminatory power of HR-pQCT was similar as for patients with preterminal renal failure (24,25). A remarkable difference between these studies and the data presented here is that the heterogeneity of trabecular structures was markedly higher in dialysis patients with fracture history compared with dialysis patients without a history of fracture, especially in women.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, owing to bone's capability of adapting its mass to mechanical loading, a significant difference in the second set is expected. The data were collected from a prior study [38] of 100 postmenopausal women with a distal forearm fracture who were compared with 105 age-matched control women without fracture. The Mayo Clinic's Institutional Review Board approved the study, and written informed consent was obtained from all subjects; the present analysis was based on de-identified data.…”
Section: Sensitivitymentioning
confidence: 99%
“…Bone microarchitecture parameters measured by HR-pQCT have been found to be associated with prevalent fracture in postmenopausal women and older men independently of areal bone mineral density (aBMD) [1][2][3][4][5]. Bone strength, estimated using micro-finite element analysis (μFEA), was also associated with prevalent fracture [6][7][8][9][10][11][12][13][14]. Moreover, HR-pQCT has been used to assess age-related bone loss [15][16][17][18][19] and to monitor variations in microarchitecture parameters during osteoporosis treatments [20][21][22][23][24][25][26].…”
Section: T R a C T A R T I C L E I N F O Introductionmentioning
confidence: 99%